Hubungan Pengetahuan Ibu tentang Stimulasi Tumbuh Kembang terhadap Perkembangan Anak Usia di Bawah Dua Tahun - Meta Aldila Listiya; Nisma Nisma; Popy Popy (Khatulistiwa Nursing Journal, 2026)
Background: Children under two years old are in a golden age, a time of rapid development. Efforts to achieve optimal development must be balanced with optimal growth and developmental stimulation. However, many mothers still do not know how to stimulate growth and development in children. The role of a mother in providing stimulation to children has a significant influence, so it’s very importand to have a good knownledge to encourage children growth optimally. Objective: The purpose of this study was to analyze the relationship between maternal knowledge about growth and development with the developmental status of children under two years old. Method: The study design used a cross-sectional. The study was conducted at the Banjar Serasan Community Health Center with a sample of 77 mothers who had children under two years old selected accidental sampling with the inclusion criteria of this study, namely with the inclusion criteria of mothers who had children aged 0-24 months, mothers who attended posyandu activities and were willing to be respondents, while the exclusion criteria were mothers with children with special needs. Data collection used research instruments consisting of a maternal knowledge questionnaire and KPSP. Result: The results of statistical tests using the Spearman Rank test showed that there was a positive relationship between maternal knowledge about growth and development stimulation and the development of children under two years of age with a p value of 0.010 (p<0.05) and a correlation coefficient (R) of 0.292. Conclusion: There was a significant relationship between maternal knowledge and the development of children under two years old.